The effect of Hp infection on dyslipidemia in Asia and out of Asia: a systematic review and meta-analysis - Quan, Kong-jin; Huang, Zhen-peng; Nie, Sha; Li, Xiao-xiao (Frontiers in Medicine, 2025)
IntroductionHelicobacter pylori (Hp) infection is a major public health problem worldwide. Similarly, millions suffer from dyslipidemia, which is a risk factor for cardiovascular and cerebrovascular diseases. This study aimed to explore whether Hp infection affects dyslipidemia.MethodsThe search databases included PubMed, Web of Science, Cochrane Library, Embase, China National Knowledge Infrastructure, Wanfang Data, Chinese sci-tech periodicals, and Sino-Med, from database construction to September 2024. Casecontrol and cross-sectional studies on Hp infections associated with dyslipidemia were included.Results and DiscussionIn total, 12 casecontrol and 28 cross-sectional studies were included. The total sample size included 274,414 cases, of which 130,529 were Hp-infected and 143,885 were uninfected. Compared to uninfected patients, Hp-infected patients abnormally elevated total cholesterol (TC) [Mean Difference (MD) = 0.15, 95% Confidence Interval (CI) 0.130.17, p < 0.05], low- density lipoprotein cholesterol (LDL-C) [MD = 0.18, (95%CI 0.140.22), p < 0.05]; TG [MD = 0.13, (95%CI 0.100.16), p < 0.05], and triglyceride (TG) levels and abnormally reduced high-density lipoprotein cholesterol (HDL-C) levels [MD = 0.02, (95%CI 0.03 to 0.01), p < 0.05]. Hp infection was correlated with dyslipidemia, and the effect of Hp infection on dyslipidemia varies in different regions.Systematic Review Registrationidentifier CRD42024626356.